Análisis a los riesgos crediticios en la Cooperativa de Ahorro y Crédito Chibuleo ltda. agencia Latacunga, ubicada en la Parroquia La Matriz cantón Latacunga al periodo del 01 de enero al 30 de diciembre del 2012 - Toaquiza Vega, Elsa Piedad (2015)
The research carried out was mainly intended to establish a series of methodological, conceptual and content tools around a correct analysis of the credit risks in the Savings and Credit Cooperative Chibuleo Ltda. Therefore tools were also created as the interviews and surveys in order to obtain important data of customers and collaborators of the institution and initiate with strategies in order to fulfill the stated objective and thus to establish recommendations for improvement about the internal debt as to well as to achieve to identify the credit riskgoes growing because of internal and external factors; internal are deficiencies within the institution which must be improved for the welfare of the Cooperative….